Genetic diversity and proximate analysis of Indonesian local mung bean (Vigna radiata) - HIGA AFZA; ENDAH RETNO PALUPI; LINA HERLINA; SATRIYAS ILYAS (Society for Indonesian Biodiversity, 2023)
Abstract. Afza H, Palupi ER, Herlina L, Ilyas S. 2023. Genetic diversity and proximate analysis of Indonesian local mung bean (Vigna radiata). Biodiversitas 24: 6377-6388. Mung bean is an important food crop because it has a high protein content. However, not much information is available about Indonesian local mung beans. This study aimed to obtain information about flowering and seed formation in local mung beans (Vigna radiata L.) to determine the genetic diversity of mung beans using simple sequence repeats and the protein, starch, fat, and ash content. Mung bean seeds of 15 genotypes were obtained from the Indonesian Agricultural Gene Bank collection. The experiment was arranged using a one-factor randomized complete block design. Genotypes with a low degree of non-synchrony of pod maturity (DDd) were Local Bima and Arta Koneng 01070. The highest fruit set was observed in the Madura Local accession (73.09%). The accumulated value of heat units was calculated as growing degree days; the heat units from planting to the first flowering ranged from 544.6-670°C and from planting to the first ripe pod (heatd2) and 90% ripe pod (heatd3) phases ranged from 819.7-933.7°C and 1,111.9-1,419.1°C. Phylogenetic tree construction was made based on scoring of the presence of alleles that appeared on the electrophoresis results of 12 microsatellite markers on 15 mung bean genotypes. The superior varieties, Vima1 and Walet, were separated from the other 13 local genotypes at a genetic similarity coefficient of 0.583. The protein contents of the tested mung bean genotypes were 19.19%-23.06%.